The role of posyandu cadres in child growth monitoring for early detection of stunting - Rahmawati, Eli; Setyawati, Ernani; Nuurwahidah, Nuurwahidah; Noviasari, Damai; Murti, Ni Nyoman; Wijayanti, Endah; Handayani, Sekar; Kusumayanti, Ita (Poltekkes Kemenkes Bandung, 2026)
Background: Stunting remains a major public health challenge with long-term consequences for the quality of human resources in Indonesia. Stunting prevention requires early detection through routine child growth monitoring conducted at Integrated Health Service Posts (Posyandu). Objective: This study aimed to analyze the relationship between knowledge and motivation and the role of Posyandu cadres in child growth monitoring as an early detection strategy for stunting in the service area of Graha Indah Public Health Center, North Balikpapan. Methods: A descriptive analytical study with a cross-sectional design was conducted. A total of 79 active Posyandu cadres were purposively selected as the study sample. Data were collected using structured questionnaires that had been tested for validity and reliability and were analyzed using Spearman’s rank correlation test. Results: The results showed that Posyandu cadres generally had good levels of knowledge and motivation and performed their roles optimally. A strong and statistically significant relationship was found between motivation and the role of cadres (p=0,001), whereas knowledge was not significantly associated with cadre roles (p=0,650). Conclusion: These findings indicate that motivation is a key factor in optimizing the role of Posyandu cadres in child growth monitoring. This study recommends strengthening cadre motivation through continuous training, intensive supervision, and performance-based incentive systems to enhance the effectiveness of early stunting detection at the community level.